MENCIPTAKAN PEMBELAJARAN KREATIF DAN KONDUSIF - Asmadawati, Asmadawati (AIN Padangsidimpuan, 2014)
AbstractCreating a creative and safe teaching on targeting effective and effision teaching needs a professional educater especially in opening and closing teaching, eleborating materials, good discussion, good in stating idea, good in using various techniques, good in managing classrom will optimalize a good teaching in creation and safety.Keywords: Teaching, creative and safe